Biologics Drugs in Behçet’s Disease: A Single Centre Experience - Pinto,Luísa Serpa (2021)
Abstract Introduction: Behçet´s disease (BD) is a systemic vasculitis of unknown cause. Several cytokines, such as tumor necrosis factor-alpha (TNF-α), appear to play a substantial role. Therefore, biologics such as anti-TNF-α agents are rising to control severe or refractory BD´s manifestations. We aimed to describe the biological therapy´s outcomes in BD patients. Methods: A longitudinal, prospective, unicentric cohort study with patients followed in a specialized outpatient clinic. We collected data regarding BD´s manifestations, treatments, and outcomes during follow-up. Results: Our cohort includes 243 patients, of whom 31% were male. During follow-up, 20 patients (8%) were treated with biological drugs. Patients who received biological therapies were younger (p = 0.030), had less frequently genital aphthosis (p = 0.009), and more frequently erythema nodosum (p = 0.009), polyarthritis (p = 0.002), spondyloarthritis (p = 0.024), retinal vasculitis (p = 0.011) and gastrointestinal manifestations (p = 0.024), namely gastroduodenal ulcer (p = 0.035), digestive bleeding from ulcers (p = 0.002), and bowel perforation (p = 0.004). Anti-TNF-α agents were used in all of these patients, most frequently infliximab. Patients started biologicals after classical immunosuppressors failure, and most went into remission (93%). Three patients developed tuberculosis during treatment, regardless of regular screening tests. It was possible to stop biological therapy in five patients, so far, without recurrence, with 33 months of mean follow-up time after suspension. Discussion: Anti-TNF-α agents are highly effective for re-fractory BD´s manifestations, although they are not innocuous. Little is known about the optimal duration of these therapies, regarding when and how to stop these drugs. This issue is essential not only to avoid relapses but also to reduce therapy side-effects.